2012
DOI: 10.1186/1475-2840-11-65
|View full text |Cite
|
Sign up to set email alerts
|

ROCK inhibitor fasudil attenuated high glucose-induced MCP-1 and VCAM-1 expression and monocyte-endothelial cell adhesion

Abstract: BackgroundPrevious studies suggested that the RhoA/ROCK pathway may contribute to vascular complications in diabetes. The present study was designed to investigate whether ROCK inhibitor fasudil could prevent high glucose-induced monocyte-endothelial cells adhesion, and whether this was related to fasudil effects on vascular endothelial cell expression of chemotactic factors, vascular cell adhesion molecule-1 (VCAM-1) and monocyte chemoattractant protein-1 (MCP-1).MethodsHUVECs were stimulated with high glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 46 publications
(53 reference statements)
4
47
0
Order By: Relevance
“…A wealth of literature suggests that RAGE/ ligand interaction induces upregulation of adhesion molecules (29,30). Here, we also observed that stimulation of HUVECs with Gla-BSA sharply increased VCAM1, ICAM1, and E-selectin mRNA, which was efficiently downregulated by anti-RAGE, indicating that Gla-BSA upregulated the expression of adhesion molecules via RAGE.…”
Section: Longistatin Suppresses Expression Of Adhesion Molecules and supporting
confidence: 71%
See 2 more Smart Citations
“…A wealth of literature suggests that RAGE/ ligand interaction induces upregulation of adhesion molecules (29,30). Here, we also observed that stimulation of HUVECs with Gla-BSA sharply increased VCAM1, ICAM1, and E-selectin mRNA, which was efficiently downregulated by anti-RAGE, indicating that Gla-BSA upregulated the expression of adhesion molecules via RAGE.…”
Section: Longistatin Suppresses Expression Of Adhesion Molecules and supporting
confidence: 71%
“…These adhesion molecules play essential roles during the recruitment of inflammatory cells into the site of insults (29,30). We provide data supporting that rlongistatin prevents the secretion of cytokines from endothelial cells induced by RAGE ligands.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The monocytes can pass through the injured or dysfunctional endothelium into the extravascular space and then differentiate into macrophages (12). These processes are partly regulated by chemotactic factors, such as endothelial VCAM-1, which directly takes part in the development of atherosclerosis as an inflammatory factor (66). The induction of adhesion molecules in vascular endothelial cells and the subsequent recruitment of circulating monocytes are proinflammatory events that promote atherogenesis and plaque instability (67).…”
Section: Discussionmentioning
confidence: 99%
“…The active form of RhoA promotes activation of the Rho kinase (ROCK) that inhibits MLC phosphatase (MLCP) activity, the dephosphorylation of myosin and subsequent relaxation [24]. Alterations in the RhoA/Rho kinase pathway is reported to be involved in endothelial dysfunction, inflammation [25,26] and with exposure to particulate matter [27]. …”
Section: Introductionmentioning
confidence: 99%